1999
DOI: 10.1079/pns19990019
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of non-nutrient plant factors: dietary flavonoids and phyto-oestrogens

Abstract: The bioavailability in human subjects of non-nutrient plant factors, including dietary flavonoids and phyto-oestrogens, is of great importance relative to their reported health protective effects. These effects include protection against heart disease, and also in the case of the phyto-oestrogens, hormone-dependent cancers. Epidemiological studies have shown flavonoid intake (mostly quercetin) to be inversely associated with mortality from CHD. Quercetin is a potent antioxidant in vitro, and protection against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 48 publications
1
66
1
1
Order By: Relevance
“…These transformation products can subsequently be absorbed from the colon, as it is established for soy isoflavones (39), to exert biological activity inside the body. While 8-PN was only one out of a large number of liver transformation products of IX (21), the human intestinal microbiota selectively converted IX into 8-PN with high conversion efficiencies (>35%).…”
Section: Discussionmentioning
confidence: 99%
“…These transformation products can subsequently be absorbed from the colon, as it is established for soy isoflavones (39), to exert biological activity inside the body. While 8-PN was only one out of a large number of liver transformation products of IX (21), the human intestinal microbiota selectively converted IX into 8-PN with high conversion efficiencies (>35%).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of endometrial hyperplasia, complex, or simple was not increased in the groups treated with isoflavones. Since isoflavones are known to possess both estrogenic and anti-estrogenic properties, 40) the result that only anti-estrogenic effects on endometrial carcinogenesis were found is considered to be related to the dose used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…39) Free genistein or daidzein as well as the corresponding glucuronidated products are absorbed, and the compounds are excreted in free form or as metabolites. 39,40) In this study, genistein and daidzein were given subcutaneously, as has been done in a number of previous studies. 14,15,41) It is thought that such isoflavones administered s.c. can be directly absorbed into the blood.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, a absorção deste flavonóide é pequena. Genisteína e daidzeína têm efeitos antioxidantes menos eficazes que a quercetina in vitromas, como são melhores absorvidas, poderiam ser suficientemente biodisponíveis para agir in vivo (58). O efeito inibidor de formação de peroxidase poderia ter implicações na DCV, na tumorigênese e também em relação ao funcionamento da tireóide (43).…”
Section: Efeitos Em Doença Cardiovascular E Trombofiliaunclassified